Extracellular nanovesicles for packaging of CRISPR-Cas9 protein and sgRNA to induce therapeutic exon skipping - Peter Gee (Nature Portfolio, 2020)
Expression of Cas9 and gRNA from viral vectors in vivo may cause off-target activity. Here the authors present NanoMEDIC, which uses nanovesicles to transiently deliver editing machinery to hard-to-transfect cells.